IMMERSIVE VIRTUAL REALITY IN PAIN RELIEF IN PATIENTS WITH BURNS: SYSTEMATIC REVIEW AND META-ANALYSIS (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: Evaluating the use of immersive virtual reality as a non-pharmacological intervention for pain relief and opioid consumption during dressing changes in patients with burn injuries. Methods: This review considered study designs, randomized clinical trials, non-randomized controlled trials, without restriction on the year of publication. An extensive search in six electronic databases (PubMed; EMBASE, Web of Science, CINAHL, Cochrane Library, Clinicaltrial.gov) was performed. RevMan version 5 software was used to carry out a meta-analysis. The certainty of the evidence was analyzed using GRADE. Results: Included 10 articles, total of 514 patients, aging 5 to 80 years old. In a combined analysis of pain variables, time thinking about pain from eight studies, the result favored the use of immersive virtual reality compared to control, the Standardized Mean Difference (SMD -0.86; 95% CI -1.22 - 0.49 N = 772 I2 = 82%). Conclusion: The evidence compiled in this review supports the use of immersive virtual reality to reduce pain.